Comparison of Mode and Channel from Operation and Investment Perspective-Case Study of Cross - border Electric Retailers - Qu, Tao; Qiu, Li-yin; Qu, Yan (Archives of Business Research, 2017)
This paper takes Amazon, Wal-Mart, Jingdong and Alibaba as examples to study the international operation mode and investment path of retail electric business. The research shows that the transition from B2C to B2B2C is the best way to avoid institutional barriers. Based on their respectively comparative advantages, it is the key to construct the service support which the supplier (B) ? the businessman (B) ? the customer (C) all need, such as logistics, payment and finance. Amazon and Wal-Mart's FBA openness and infrastructure sharing model are conducive to consolidate the supply chain to ensure the genuine sources of products and their low prices ; Alibaba uses strong relationship-building capacity and integration of external resources to create a fourth party logistics platform; increases customer stickness through making use of Alipay to collect large amount of leisure funds to do consumer finance innovation. Regardless of the path, countries with close geographical and psychological distance or with good infrastructure are preferred in case enterprises' overseas investment. The fighting focus of the next step is to remodel the business under the premise of following the existing business structure and based on cloud computing.